No man's land : - Tanovič, Danis; Dumas-Žajdela, Frédérique; Baschet, Marc; Kolar, Čedomir; Djurič, Branko (Thames & Hudson ;, 2001)
Set during the height of the Bosnian War in 1993, a group of Bosnian soldiers are advancing on Serb territory under the cover of a foggy night. At daybreak, the fog lifts, and the Serbs open fire. Soon there is only one Bosnian survivor because he was able to dive into a trench in no man's land. He then watches as two Serbian soldiers use the body of a fallen Bosnian to bait a land mine. He fires on them, killing one, and taking the second hostage. Now both are alone and equally armed, so they are forced to share a wary trust as they try to attract help from either side.